Mevsılî’nin El-İhtiyâr’ında maslahat düşüncesi - Avcı, Fatih (My University, 2017)
Bu çalışma Hicri 7. yy’da Irak-Kûfe bölgesinde yaşamış Hanefi âlim Abdullah b. Mahmud el-Mevsılî’nin el-İhtiyâr li Ta’lili’l-Muhtâr adlı eserindeki maslahat düşüncesini incelemek üzere kaleme alınmıştır. Çalışma giriş ve iki bölümden oluşmaktadır. Giriş bölümünde Mevsılî’nin hayatından kısaca bahsedildikten sonra maslahat düşüncesinin mahiyeti ve Hanefi fıkhındaki yeri ele alınmıştır.Birinci bölümde el-İhtiyâr’da kulların maslahatını te’min için kullanılan şer’î deliller ve yedi küllî kâide ele alınmıştır. İkinci bölümde ise Mevsılî’nin el-İhtiyâr adlı eserinde verdiği örneklerden yola çıkarak maslahat kavramı ve türleri incelenmiştir. Mevsılî, el-İhtiyâr, Maslahat, Hüküm.

This thesis has been written to study and analyze the maslaha (the people’s benefit) theory of a Hanafi scholar who lived in the Iraqi-Kufa region in the 7th century of Hijra: Abdullah b. Mahmud al-Mawsili, depending on his important work al-Ihtiyar li Ta'lili’l-Muhtar.The work consists of introduction and three chapters. In the introduction, after a brief biography of Mavsili, the nature of maslaha thought in Islamic Law and its place in the Hanafi doctrine have been discussed. In the first chapter the sources of Islamic law (adilla al-shar‘iyyah) which are used to enshure the peoples benefit in al-Ihtiyar and legal maxims (al-qawaid al-kulliyyah) have been studied. In the second chapter the concept of maslaha in Islamic law and its various types have been examined based on the examples given in al-Ihtiyar. Mawsili, al-Ikhtiyar, al-Maslaha, Rule.
Keywords: Hukuk; İslam dini; İslam hukuku